MAHAR: PERSPEKTIF AL-QUR’AN DAN IMPLEMENTASINYA PADA MASYARAKAT KABUPATEN KONAWE - Irdawati Saputri (Jurnal Ushuluddin Adab dan Dakwah, 2018)
This study discusses the subject matter of Mahar Perspektif al-Qur'an and its Implementation on Konawe Regency Community, This research aims to: 1) To study the existence of dowry for Tolaki community in Konawe District; 2) To examine the urgency of dowry for the Tolaki community in Konawe District; 3) To examine the implementation of the giving of mahar to Tolaki people of Konawe Regency. Types of Research is field research (field research) whose procedures produce descriptive data using the approach of science of tafsir, juridical and phenomenology. Data collection methods used are observation, interviews, documentation and tracing of various literatures or references. This study uses observation guides, interview guides and documentation data as Research Instruments. Processing techniques and data analysis is done through three stages, namely data reduction, data presentation, and the conclusion and verification of data. The results of this study indicate that the existence Mahar in Tolaki known by Popolo or Kinaweoako. The form is not bound but generally in Tolaki society there are two that is in the form of money and in the form of objects. The form of money is divided into two forms: 88 real and Rp. 264,000. Mahar to Tolaki tribe in Konawe District still exist in determining the number, and remain in the corridor of al-Qur'an there are only few steps that must be done accompanied by custom settlement. The general objective of the dowries on the Tolaki tribe is as a form of appreciation to women. Adat obliges the dowry so that in the future there is no mutual embarrassment to each other, both in terms of husband and wife or both families of the bride. Implementation of dowry on Tolaki Society is the process of giving mahar to Tolaki Tribe is in a series of custom known as Mowindahako procession, after the customary settlement then followed by Islamic wedding procession is usually executed in general society. Re-analyzing the dowry pricing case and the process of giving it into the adat series, is essentially not burdensome to the bridegroom but because of the numerous customs and customs requirements proposed by adat not to make the bridegroom run with the term mombolasuako. Thus reducing the value of family and social values. Basically the dowry is a property entitled to be earned by a wife to be given by the husband. Giving sincerely is not from the coercion factor of the bride's family. So the creation of peace in the hearts of the bridegroom in marriage. Seeing the implementation of giving dowries to the Tolaki community, especially those living in Konawe District can follow the marriage procession based on Islamic law by integrating it with cultural values that have relevance to the Islamic Syari'ah.